The ecological and evolutionary importance of immune system variation in the three-spined stickleback - Robertson, Shaun (2016)
Placing our understanding of the function of the immune system into a more natural setting remains a fundamental challenge in biology, particularly how natural variation shapes the immune response and what the evolutionary consequences of such variation are. In this thesis, I use the three-spined stickleback as a model system for wild immunological studies. First, I developed a set of markers to measure the expression levels of key immune system genes using quantitative real-time PCR, representing the innate and adaptive immune response, and then used them to address a number of questions. I demonstrated that there are underlying differences in innate and adaptive gene expression levels between populations, as well as in innate immune response potential, which may reflect the contrasting challenges faced in these populations. By sampling individuals from multiple wild populations, I was able to demonstrate how a range of factors contribute to shaping immune system function, including sex, reproductive status, and infection with the common parasites Schistocephalus solidus and Gyrodactylus arcuatus. Next, I exposed laboratory raised fish to natural conditions and examined their response. Again, a range of factors where identified which appear to shape immune expression levels, particularly reproductive investment and infection with G. arcuatus. I also used this approach to demonstrate that immune system variation can be linked to Eda genotype, the gene which controls lateral plate phenotypic divergence during adaptive radiations. Finally, I performed a controlled infection experiment in the laboratory to show that both the innate and adaptive systems respond to Gyrodactylus infection. This thesis provides the basis for further immunological studies in stickleback, and adds to our growing understanding of the relevance of natural variation in shaping the immune response.